2015
DOI: 10.1002/cbdv.201500027
|View full text |Cite
|
Sign up to set email alerts
|

α‐Glucosidase Inhibitors from the Fungus Aspergillus terreus 3.05358

Abstract: One new diketopiperazine alkaloid amauromine B (1), along with three known meroterpenoids, austalide B (2), austalides N and O (3 and 4), and two known steroids (5 and 6), was isolated and identified from the culture broth of the fungus Aspergillus terreus 3.05358. Their structures were elucidated by extensive spectroscopic techniques, including 2D-NMR and MS analysis, the absolute configuration of 1 was unambiguously established by single crystal X-ray diffraction analysis. All the isolates were evaluated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…Marine natural products (NPs) are an important source for developing new drugs, especially those from marine-derived fungi which possess novel structures and significant biological activities [1,2]. Aspergillus is a kind of productive fungal genus and has been reported to produce many new NPs [3], such as alkaloids [4,5,6], diketopiperazines [7,8], xanthones [8], and diphenyl ethers [9]. However, the whole genome sequencing studies of fungi have indicated that most genes of fungi were silent and not expressed in the conventional experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Marine natural products (NPs) are an important source for developing new drugs, especially those from marine-derived fungi which possess novel structures and significant biological activities [1,2]. Aspergillus is a kind of productive fungal genus and has been reported to produce many new NPs [3], such as alkaloids [4,5,6], diketopiperazines [7,8], xanthones [8], and diphenyl ethers [9]. However, the whole genome sequencing studies of fungi have indicated that most genes of fungi were silent and not expressed in the conventional experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…α ‐Glucosidase inhibitory activities of compounds 1 – 4 were evaluated employing the method we previously reported …”
Section: Methodsmentioning
confidence: 99%
“…Solid-state fermentation the mushroom Hericium erinaceus (Tibet, China) produced 10 new isoindolin-1-ones, erinacerins C–L ( 189 - 198 ) (Figure 4 ), most of which possessed α-glucosidase inhibition with IC 50 values of 5.3–145.1 μM (acarbose, 382.7 μM) (Wang et al, 2015f ). Aspergillus terreus CGMCC 3.05358 produced amauromine B ( 199 ), a novel diketopiperazine alkaloid which displayed more potent α-glucosidase inhibition than reference acarbose with IC 50 values of 0.30 and 0.66 mM, respectively (Shan et al, 2015 ). Asperterpene B ( 200 ) possessing a noval 1,2,5-trimethyl-4,9-dioxobicyclo[3.3.1]non-2-ene-3-carboxylic acid moiety, was produced by soil-derived A. terreus (Yangzi River, Hubei, China), and was a growth inhibitor of BACE1 with an IC 50 of 59 nM (positive control LY2811376, 260 nM) (Qi et al, 2016 ).…”
Section: Terrestrial Microorganismsmentioning
confidence: 99%